On Mappable Nearly Orthogonal Arrays Using Projective Geometry: A Mathematical Approach - Poonam Singh; Mukta D. Mazumder; Santosh Babu (Mathematics and Computer Science: Contemporary Developments Vol. 1, 2024)
Finite projective geometry is used to construct many series of symmetric orthogonal arrays of strength two and more. This chapter proposes a method for constructing nearly orthogonal arrays mappable into fully symmetric orthogonal arrays of strength two using finite projective geometry. Mappable nearly orthogonal arrays are designs used in optimization, particularly in situations where factors interact with each other. They provide an efficient way to study stratification and understand complex systems by minimizing experimental runs while maximizing the number of factors.